Inter-hospital transfer for neurosurgical management of mild head injury in a developing country: A needless use of scarce resources? - D O Okonkwo; Amos Olufemi Adeleye (The Indian Journal of Neurotrauma, 2011)
Some authorities in the world’s industrialized nations now believe that the care of patients with mild (and even some moderate) head injury (MiHI) in general is an unnecessary additional burden on their already over-tasked neurosurgical workforce. There is a high rate of inter-hospital transfer for neurosurgical evaluation of cases of MiHI in Nigeria, an African developing country. This may be needless in many cases. We therefore conducted a prospective in-hospital cohort study of cases of MiHI managed in a new neurosurgical service in a Nigerian university teaching hospital over an 8-month period. Clinical and in-hospital outcome characteristics of the cases were analysed and presented in descriptive statistics. Subgroup analysis was then carried out between cases presenting directly post-trauma in our unit and those referred to us for neurosurgical management from other health facilities. Inferences were made based on the chi-squared test and the 2-tailed t-test, and the significant level was set at p < 0.05. Eighty-four cases of MiHI were analysed, 72 males, 12 females. The causative trauma was road traffic related in 65.5%, and 25.0% had other extracranial injuries. The admission GCS was 14 or 15 in 93%. Seventy percent of the cases were referred from other (including tertiary) medical facilities. With mean length of stay of 6.15 days, the over-all inhospital good vs poor outcome rates were 97.6 vs 2.4% on the dichotomised GOS. There was no significant difference (p > 0.10) between the two subgroups with respect to either the post treatment in-hospital outcome variables, or in their clinical determinants.Majority of the cases of mild head injury that were so treated in this study population did not need the inter-hospital transfer for neurosurgical management. Large studies are needed to determine the clinicopathologic indices predictive of the few cases that may be an exception to this assumption.